Murder on the highway : the Viola Liuzzo story - Siegel, Beatrice (New York : Four Winds Press ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1993)
Presents the life of the civil rights worker who was murdered shortly after the 1965 march from Selma to Montgomery, Alabama, and discusses the rights of Afro-Americans living in the South prior to and following her death.
Includes bibliographical references (p. 118-120) and index.
Keywords: Liuzzo, Viola, -- 1925-1965 -- Juvenile literature; Liuzzo, Viola, -- 1925-1965.; Civil rights workers -- Alabama -- Biography -- Juvenile literature; African Americans -- Civil rights -- Alabama -- Juvenile literature; Civil rights movements -- Alabama -- History -- 20th century -- Juvenile literature; Civil rights workers; Civil rights -- History; African Americans -- Civil rights; Alabama -- Race relations -- Juvenile literature